The Role of Internal Auditors in Control Self Assessment in the Material Planning Field of Automotive Company PT. Alkha - Andi Martias; Agni Isador Harsapranata; Ahmad Rais Ruli; Rahma Wiyanti; Rahmat Novari (Future Science, 2022)
Control Self Assessment (CSA) has various benefits for a company or organization that implements it because it provides great added value in improving the operational performance of the company or organization. The process of implementing the Control Self Assessment (CSA) continues to be developed and implemented so that the benefits can be felt because it reveals the broad problems involved in the risk control concept. Control Self Assessment (CSA) is a process where management from all levels continuously builds awareness on all important factors that can affect the achievement of goals so as to enable them to make the necessary adjustments (create control). The company in this case the management cooperates with the Internal Audit and Risk Management Unit in an effort to develop the Risk Management. The Internal Auditor is required to carry out his role as a consultant to facilitate the development of Risk Management in the company. The structure of the ALKHA automotive company has several fields, each of which has a specific work process. With the Control Self Assessment method, all fields identify the inherent risks inherent in the work process as well as the mitigation activities that must be carried out. This paper will present in detail the technical implementation and results of the Control Self Assessment in the ALKHA work area, namely the Material Planning field. Errors that arise due to the application of CSA can be negligence of the PIC concerned but also due to weak dual control (dual control) from related parties. Analysis of the data in this paper, several conclusions can be drawn that internal auditors have an important role in facilitating Control Self Assessment of business processes in the Materials Planning sector.